2008
DOI: 10.1007/s10936-008-9091-1
|View full text |Cite
|
Sign up to set email alerts
|

Constituent Length Affects Prosody and Processing for a Dative NP Ambiguity in Korean

Abstract: Two sentence processing experiments on a dative NP ambiguity in Korean demonstrate effects of phrase length on overt and implicit prosody. Both experiments controlled non-prosodic length factors by using long versus short proper names that occurred before the syntactically critical material. Experiment 1 found that long phrases induce different prosodic phrasing than short phrases in a read-aloud task and change the preferred interpretation of globally ambiguous sentences. It also showed that speakers who have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 21 publications
2
47
1
1
Order By: Relevance
“…The advantage of the visual-toauditory cross-modal priming paradigm presented here is that a very brief and simple diagnostic allows grouping participants based on certain prosodic phenomena, so that implicit prosody can then be studied without comparison of implicit and overt prosody on a sentenceby-sentence basis. Indeed, our results suggest that such comparisons, as have been done in previous work (Bergmann & Ito, 2009;Foltz et al, 2011;Hwang & Schafer, 2009), may not be useful: rather, measurable general characteristics and tendencies found in overt prosody from reading aloud can be used to predict implicit prosodic behavior and group participants based on these predictions to then see if the cross-modal priming paradigm may be used to confirm the predictions. However, since the current experiments differ from the previous work in that they test cross-sentential pitch accent patterns rather than implicit prosodic phrasing, this conclusion may be premature.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The advantage of the visual-toauditory cross-modal priming paradigm presented here is that a very brief and simple diagnostic allows grouping participants based on certain prosodic phenomena, so that implicit prosody can then be studied without comparison of implicit and overt prosody on a sentenceby-sentence basis. Indeed, our results suggest that such comparisons, as have been done in previous work (Bergmann & Ito, 2009;Foltz et al, 2011;Hwang & Schafer, 2009), may not be useful: rather, measurable general characteristics and tendencies found in overt prosody from reading aloud can be used to predict implicit prosodic behavior and group participants based on these predictions to then see if the cross-modal priming paradigm may be used to confirm the predictions. However, since the current experiments differ from the previous work in that they test cross-sentential pitch accent patterns rather than implicit prosodic phrasing, this conclusion may be premature.…”
Section: Discussionmentioning
confidence: 75%
“…These studies have shown mixed results. For example, Jun and Kim (2004; see also Hwang &Schafer, 2009, andJun &Koike, 2003, for similar experiments with Japanese) conducted production experiments with Korean relative clauses, recording readers who either skimmed a text and then read it aloud, or read aloud without skimming. Participants then completed an off-line syntactic judgment task for the same sentences.…”
Section: Introductionmentioning
confidence: 99%
“…Speakers shift overt prosodic patterns, depending on phrase length (Fernández et al, submitted;Hirose, 2003). Likewise, silent readers seem to rely on phrase length to generate subvocal prosodic phrasing, which in turn affects syntactic parsing (Hwang & Schafer, 2009;Hirose, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Even when lexical and semantic factors are largely negated using Jabberwocky sentences, prosodic phrasing affects attachment preferences (Wijnen,66 2004). The finding that the phonological weight of a relative clause (a prosodic feature) influences parsing decisions has been replicated in Korean (Hwang & Schafer, 2009;Jun & Kim, 2004) and German (Wijnen, 2004).…”
Section: Implicit Prosody Hypothesis Does the Reader Imbue Written Lmentioning
confidence: 90%
“…A short relative clause (e.g., who cried) cannot form its own prosodic phrase (including a prosodic break), and hence it attaches itself to the preceding words, resulting in local attachment (late closure) (Fodor, 2002a;Jun & Kim, 2004). However, long relative clauses (e.g., who cried all through the night) are processed as one intonational phrase predisposing the reader to high attachment or early closure (Hwang & Schafer, 2009;Jun, 2010). Prosodic phrasing has been manipulated by varying the length of noun phrases and relative clauses.…”
Section: Implicit Prosody Hypothesis Does the Reader Imbue Written Lmentioning
confidence: 99%